Answer:
Demetrius's account is $84 higher after the two transactions
Step-by-step explanation:
Let
x -----> original amount in Demetrius's account
y ----> amount in Demetrius's account after the deposit and the withdraws
we know that
The amount in Demetrius's account after the two transactions must be equal to the original amount in Demetrius's account plus the deposit minus the withdraws
so
![y=x+120-36](https://tex.z-dn.net/?f=y%3Dx%2B120-36)
![y=x+\$84](https://tex.z-dn.net/?f=y%3Dx%2B%5C%2484)
therefore
Demetrius's account is $84 higher after the two transactions
Answer:
D
Step-by-step explanation:
given the 2 equations
x + 2y = 27 → (1)
2x + 3y = 46 → (2)
Rearrange (1) expressing x in terms of y by subtracting 2y from both sides
x = 27 - 2y ← substitute into (2)
2(27 - 2y) + 3y = 46
54 - 4y + 3y = 46
54 - y = 46 ( subtract 54 from both sides )
- y = - 8 ( multiply both sides by - 1 )
y = 8 → D
No it is not a complete sentence
X=6 because
9-6=3
X=3 because
2•3=6
X=2 because
1.5 or 1 1/2 • 2 = 3
Not sure if this was what you needed or not!
Answer:
-199
Step-by-step explanation:
- put -6 in place of x in equation